Arthroscopic Broström-Gould repair for lateral ankle stabilization in adolescent patients has comparable outcomes to that of open - Neeraj Mishra; Chloe Xiaoyun Chan; Chay-You Ang; Derrick Jun Liang Lam; Kenneth Pak Leung Wong; Guan Tzu Tay; Ashik Bin Zainuddin Mohammad (Journal of Orthopaedic Reports)
Background: Existing literature indicates positive outcomes with the arthroscopic Broström-Gould technique as a viable alternative to the established open procedure in adults. Nevertheless, there exists a dearth of comparative studies focusing on adolescents.The objective of this study was to evaluate and contrast the clinical results of adolescents undergoing either arthroscopic or open Broström-Gould techniques over a 2-year follow-up. Methods: We conducted a retrospective comparative analysis on patients aged 18 years and below, who underwent either arthroscopic or open Broström-Gould procedures for chronic lateral ankle instability during the period spanning January 2014 to December 2016.The study included cases with at least 2-year follow-up. Key parameters such as age, sex, race, concomitant procedures, surgery duration, hospital stay length, and post-operative complications were documented. Additionally, the assessment of clinical outcomes involved the utilization of the Foot and Ankle Outcome Score (FAOS) at the 6-month post-operative follow-up. Results: Seven arthroscopic and 13 open procedures were conducted, and no statistical differences were observed in patient demographics and pain scores. The open group exhibited a notably reduced duration of surgical procedure (open: 77.8 ± 17.6 min; arthroscopic: 100.7 ± 24.1 min; p = 0.03). Hospital stays and FAOS scores at 6 months were similar between the groups. Two complications occurred in the open group, involving suboptimal pain control and deep infection requiring re-admission and repeated surgeries. No complications were reported in the arthroscopic group, and only one patient in this group had concomitant preoperative intra-articular abnormalities. Conclusions: The arthroscopic Broström-Gould technique yields clinical outcomes similar to the open technique in addressing chronic lateral ankle instability in adolescents, and it exhibits lower complication rates.